Various Phenotypes related with Epilepsy in Autoimmune Encephalitis - Lal Chand Dhingra, Deepak Kumar, Zuhaib Ahmed Soomro, Abdul Ghafoor Magsi, Najam-us-Saqib Ansari, Ishfaque Ahmed Simair, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To observe and analyses the epileptic phenotypes in autoimmune encephalitis ranging from acute symptomatic-seizures to autoimmune related epilepsy. Study design: Retrospective-observational cohort study Place and duration of study: Ghulam Muhammad Mahar Medical College Sukkur and Shaheed Mohtarma Benazir Bhutto Medical University Larkana from 1st August 2020 to 30th September 2021. Methodology: One hundred and twenty seven patients who were enrolled with a new onset of seizures in reference to autoimmune encephalitis. Clinical as well as through para-clinical tests, including electroencephalogram, cerebrospinal fluid/neuroimaging techniques including magnetic resonance index or fluorine-18-fluorodeoxyglucose positron-emission tomography/computed tomography was used for confirming the cases. Each patient underwent anti-nuronal antibody test and was grouped as positive or negative for the test and clinically compared. Results: There were 66 (51.96%) females and 61 (48.04%) males with mean age was 54±5.5 years. There were 62.9% cases who were having anti-neuronal antibodies as positive while 37.1% had a negative result. Majority of the positive group had multiple type seizures whereas SE was more common in negative group cases. There were 111 (87.4%) cases were given immunotherapy. Within these 111 cases the immunotherapy was effective in 60% of the cases. There were 81% cases with psychological as well as cognitive disturbances with 43.75% having long term sequel. The most common phenotype for seizure was focal impaired awareness seizures followed by focal bilateral tonic clonic seizures. Conclusion: Early onset of immunotherapy and recognition of seizures may avoid long term irreversible outcomes of sequela. Key words: Epileptic phenotype, Autoimmune encephalitis, Acute symptomatic seizure, Autoimmune associated epilepsy